2005
DOI: 10.1111/j.1523-1755.2005.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal replacement therapy for diabetic end-stage renal disease: Data from 10 registries in Europe (1991–2000)

Abstract: This report has shown that during the last decade there has been a marked increase in the incidence of RRT for type 2 DN. Survival analysis showed that over the period 1991-1999 the mortality rates of all dialysis patients and of type 1 diabetic and nondiabetic renal transplant recipients have fallen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
91
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(103 citation statements)
references
References 22 publications
6
91
1
5
Order By: Relevance
“…18 Serum albumin is a strong predictor of mortality 11,12 and related to nutritional and inflammatory status. 19 Epidemiologic studies have confirmed that low serum albumin levels are frequent in HD patients, the prevalence being nearly unchanged in the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…18 Serum albumin is a strong predictor of mortality 11,12 and related to nutritional and inflammatory status. 19 Epidemiologic studies have confirmed that low serum albumin levels are frequent in HD patients, the prevalence being nearly unchanged in the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible contributory factor is a longer life expectancy of ESRD patients compared with the past. 5,6 GN is the most commonly recognized cause of ESRD worldwide. 7,8 In our study, the underlying cause of ESRD was unclear in the majority of the patients.…”
mentioning
confidence: 99%
“…7 During the past decade, the number of elderly patients and patients who had diabetes and received renal replacement therapy (RRT) increased rapidly. [3][4][5][6][7][8][9] Population aging, increased prevalence of diabetes, improved management of cardiovascular diseases, and improved access to RRT may explain this evolution. [3][4][5][6][7][8][9] In dialyzed patients, survival after first RRT in the incident cohort is usually analyzed using survival curves drawn by Kaplan-Meier or actuarial methods 10 and using Cox regression in multivariate analysis.…”
mentioning
confidence: 99%